Transformações das práticas nomeadoras no município de Marechal Cândido Rondon-PR - Colling, Patrícia Helena Frai (2022)
When naming a son or a daughter, the name giver wants their offstpring to be ideintified as belonging to the society in which they live. Being product of name givers’ choice, personal names (anthroponyms) are connected to beliefs and cultural values from those who atribute them. In regard to the forename as part of the civil name, there might be different motivations underlying the choice. In that direction, the objective of this dissertation is to show whether the modernization process has influenced the name giving practice in Marechal Candido Rondon city, Parana state, considering the hypothesis which secularization, indivivualism and globalization processes may transform the anthroponymic norms in a community. In that perspective, from the historic and social context of the place, the following research questions were addressed: would secularization have changed the practice of giving religious names? Would giving names of grandparents and parents highlight a cultural tradition? What is the use dynamics of forenames within the rise of cultural industry? Would individualism, attatched to the modernization process, have influenced the way of giving names? In order to answer those questions, the dissertarion was grounded on the theoretical assumptions from socio-onomastics (DICK, 1992; GUÉRIOS, 1981 VAN LANGENDONCK, 2007) in interdisciplinar studies from Anthropology, Sociology and History (GIDDENS, 1991; GERHARDS; HACKENBROCH, 2000; ZEPEDA, 2010; PINA CABRAL, 2007; SCARPIM, 2010). Regarding research methodology, qualitative and quantitative research were carried out by using a name bank with information on the choices of 250 juxtaposed names obtained by semi-structured interviews with name givers and name receivers. (FRAI, 2016). The interviewees were selected according to decade of birth, thus, the data correspond to a diachronic cut which encompass the decades 1930/1940, 1950, 1960, 1970, 1980, 1990, 2000 and 2010. The results of the investigations point to a divergence between the choice of feminine and masculine names in different decades. Religious names were widely used in the first decades of the analysis, mainly among women, because it resembled the active presence of the church within the consolidating community. As for masculine forenames, the main motivation was honoring the family, for it strongly resembled the social structure of germanic and italian communities. The secularization process shows that those traditional practices are no longer used, and forenames whose motivation resembles individualism become more frequent: anthroponyms chosen for being unique and different according to the name givers’ perspective, an influence of cultural industry resembling values other than those used during the colonization period. The analysis presented along this dissertation shows that the modernization process has influenced the anthroponymic norm in the city: the family and religious motivation falls into disuse at the expense of motivations which contemplate ‘unique’ names to the name givers. Motivations of religion were less frequent as more 'popular' names have increased. Homage to grandparents and parents - fatherly figures - highlighted a family core established around the the masculine figure. Anthroponyms following trends have revealed a particular preference by parents to making their children exclusive in the community. In this bias, this research contributes to the socio- onomastics since it enables a deeper understanding on the relation between naming processes and social changes in Marechal Candido Rondon city.